INTERNALIZING RELIGIOUS VALUES THROUGH HABITUATION AND MODELING METHODS IN SEKOLAH RENDAH INTEGRITAS TERAS ISLAM (SRITI) AL-QAWWAM - Maisarah, Maisarah; Maisarah; Nur Rohman; Abidah; Syafinaz Binti Salleh (Jurnal Ilmiah Didaktika, 2026)
The increasing exposure of students to digital influences has raised concerns about the weakening of religious character in elementary education. Grounded in Thorndike’s learning theory and Bandura’s Social Learning Theory, this study examines how habituation and modeling contribute to the internalization of religious values at Sekolah Rendah Integritas Teras Islam (SRITI) Al-Qawwam. Previous studies have mainly focused on routine practices without exploring the integration of habituation and modeling within a structured system adapted to students’ developmental stages. This study employed a descriptive qualitative design involving a principal, two teachers, and two students selected through purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using thematic analysis. The findings show that religious values are internalized through structured daily activities such as greetings, congregational prayers, tahfidz, cleanliness practices, and qailullah. These are implemented based on students’ developmental levels and reinforced through teacher modeling. The integration of repetitive practices and observable behaviors fosters discipline, responsibility, and spiritual awareness. This study highlights the synergy between behaviorist and social cognitive approaches and emphasizes the importance of structured habituation supported by teacher modeling in developing sustainable religious character.